1993
DOI: 10.1042/bj2950131
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the predominant glycosaminoglycan-attachment site in soluble recombinant human thrombomodulin: potential regulation of functionality by glycosyltransferase competition for serine474

Abstract: Thrombomodulin (TM) is an endothelial cell thrombin receptor that converts thrombin from a procoagulant to an anticoagulant enzyme. It has previously been shown that TM is expressed in both a high-M(r) form containing chondroitin sulphate and a low-M(r) form lacking this modification. Site-directed mutagenesis of a soluble human TM derivative (TMD1) was employed to determine the attachment site(s) of this functionally important oligosaccharide on the core protein. Although there are four serine residues within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 72 publications
2
31
0
Order By: Relevance
“…Hence, the binding of chondroitin sulfate seems to be important for several of the versatile functions of TM and to affect its cell-surface anticoagulant potential. Chondroitin sulfate is linked to Ser-474 in the high molecular weight TM of recombinant TM, but Ser-474 is also modified with a small substituent in the low molecular weight TM (9,10). By way of explanation of the fact that TM is expressed in two distinct forms, Gerlitz et al (9) postulated a model involving glycosyltransferase competition between xylosyltransferase and N-acetylgalactosaminyltransferase for Ser-474, whereas Lin et al (10) suggested that occupation of the adjacent O-linked glycosylation may be important because of the steric hindrance for xylosyltransferase of the cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the binding of chondroitin sulfate seems to be important for several of the versatile functions of TM and to affect its cell-surface anticoagulant potential. Chondroitin sulfate is linked to Ser-474 in the high molecular weight TM of recombinant TM, but Ser-474 is also modified with a small substituent in the low molecular weight TM (9,10). By way of explanation of the fact that TM is expressed in two distinct forms, Gerlitz et al (9) postulated a model involving glycosyltransferase competition between xylosyltransferase and N-acetylgalactosaminyltransferase for Ser-474, whereas Lin et al (10) suggested that occupation of the adjacent O-linked glycosylation may be important because of the steric hindrance for xylosyltransferase of the cell line.…”
Section: Discussionmentioning
confidence: 99%
“…The protein possesses five potential N-linked glycosylation sites (7) as deduced from its amino acid sequence, whereas the detection of GalNAc suggests the presence of Olinked sugar chains (8). Although uTM does not contain a glycosaminoglycan, recombinant TM and some TMs obtained from cultured human endothelial cells are expressed in both a high molecular weight TM containing chondroitin sulfate and a low molecular weight TM lacking this modification (9,10). Recombinant TM expressed in Chinese hamster ovary cells contains chondroitin 4-sulfate (11).…”
mentioning
confidence: 99%
“…52 In brief, the APCs were serially diluted in buffer consisting of 150 mM NaCl, 20 mM Tris-HCl pH 7.40, and 2 mg/ml BSA. APTTs were then determined by preincubating 20 l of the APC dilution (or buffer alone, baseline control) with 50 l of citrated plasma and 50 l of APTT reagent (Helena Laboratories 5385) for 5 min at 37°C in a 96-well plate (CoStar 3596).…”
Section: Aptt Assaymentioning
confidence: 99%
“…The situation is additionally complicated by the fact that established attachment sites are not necessarily used regularly, giving rise to so-called part-time proteoglycans. This has been considered as a result of the possibility that the attachment site is not always recognized by xylosyltransferase and that there may be competition for substrate between xylosyltransferase and glycoprotein N-acetylgalactosaminyltransferase (8). Furthermore, in the glycosaminoglycan-free form of the part-time proteoglycan thrombomodulin, the respective serine residue is substituted with the linkage region tetrasaccharide GlcA␤1-3Gal␤1-3Gal-␤1-4Xyl (9), raising the possibility that it is the transfer of the fifth monosaccharide (either GalNAc or GlcNAc) that represents the most critical step in glycosaminoglycan chain biosynthesis.…”
mentioning
confidence: 99%